(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The article focuses on adult education-androgogics. The purpose of adult education may be to become professional, social, entertaining or self-developing. Educating and educating adults will enable people to develop and realize their rights and acquire the necessary knowledge, skills, virtues and values so that they can become the owners of their destinies. Andragogics is available all over the world today. The Curriculum GlobALE global course, which provides data covering all continents, is unique for its own purposes and incorporates international support for the professionalization of the adult education sector